2019
DOI: 10.3892/ol.2019.11152
|View full text |Cite
|
Sign up to set email alerts
|

NRSN2 promotes breast cancer metastasis by activating PI3K/AKT/mTOR and NF‑κB signaling pathways

Abstract: Breast cancer is a leading cause of cancer-associated mortality globally amongst gynecologic tumors due to aggressive metastasis. A previous study reported that neurensin-2 (NRSN2) was implicated in human cancer cells, and that NRSN2 gene and protein expression levels were significantly upregulated in human breast cancer tissues compared with adjacent non-tumor tissues. The purpose of the present study was to analyze the role of NRSN2 in the metastasis of breast cancer cells and explore its potential mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(26 reference statements)
1
9
0
Order By: Relevance
“… 36 Overexpressing NRSN2 is concerned with malignant phenotype of cancers, such as ovarian cancer 37 and breast cancer. 38 In this study, the binding relationships between MALAT1 and miR-143, and miR-143 and NRSN2 were confirmed using dual-luciferase reporter gene assay. miR-143 expression was downregulated and NRSN2 expression was upregulated in EVs-treated osteosarcoma cells.…”
Section: Discussionsupporting
confidence: 52%
“… 36 Overexpressing NRSN2 is concerned with malignant phenotype of cancers, such as ovarian cancer 37 and breast cancer. 38 In this study, the binding relationships between MALAT1 and miR-143, and miR-143 and NRSN2 were confirmed using dual-luciferase reporter gene assay. miR-143 expression was downregulated and NRSN2 expression was upregulated in EVs-treated osteosarcoma cells.…”
Section: Discussionsupporting
confidence: 52%
“…As the downstream molecules, mTOR and NF‐κB were found to exhibit potential reciprocal regulation in tumor cells (Radhakrishnan et al, 2013; Ren et al, 2020; Tanaka et al, 2011; Wu et al, 2016). It has been shown that mTOR is able to positively mediate the activity of NF‐κB by stimulating the activation of IKK (inhibitor of κB kinase) in tumor cells (Dan et al, 2008; Zeng, Yin, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Its postnatal neuronal expression indicates that it might regulate synaptic functions [49]. Several studies in cancer models suggest that Neurensin-2 regulates the PI3K/AKT/mTOR pathway in an unknown mechanism [50][51][52]. In the context of depression, this pathway is specifically implicated in the induction of the synaptic translation of AMPAR and its incorporation into the postsynaptic membrane to form new synapses [13].…”
Section: Antidepressants and Neurensin-2 Modulate Ampar Signaling In mentioning
confidence: 99%